A Bernstein inequality for exponentially growing graphs. Issue 20 (18th October 2018) - Krebs, Johannes T. N.
ABSTRACT: In this article, we present a Bernstein inequality for sums of random variables which are defined on a graphical network whose nodes grow at an exponential rate. The inequality can be used to derive concentration inequalities in highly connected networks. It can be useful to obtain consistency properties for non parametric estimators of conditional expectation functions which are derived from such networks.